Pengaruh Latihan Vokal terhadap Perubahan Kemampuan Menelan pada Pasien Stroke Infark di Ruang Cempaka Rumah Sakit Umum Daerah Dr. Slamet Garut Tahun 2015 - Zahara Farhan (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2018)
Stroke infarction occurs due to disturbances in neurological system such as loss of motor function, sensibility and loss of consciousness due to tissue death due to oxygen supply to the brain is disrupted. Manifestations are impaired ability to swallow. One of the interventions to address the impaired ability to swallow, namely vokal exercises. This study aimed to influence vokal exercises to changes in swallow ability stroke infarction in room Cempaka dr. Slamet Garut Hospital. This study was conducted in May - June 2015 in room Cempak dr. Slamet Garut Hospital using a quasi experimental design. The sampling technique used purposive sample of 10 respondent. Date collection used observation checklist sheet and direct observations of researchers. The hypothesis test usedis Mann-Whitney. Hypothesis test results showed there are significant (p 0.004) vokal exercises to changes in the patient's ability to swallow infarction stroke at Cempaka Room dr. Slamet Garut Hospital with a meanof the ability to swallow priorto the vokal exercises of 3.00 and after the vokal exercises of 5.50.The results could be used as reference material and consideration for physicians and nurses in dealing with stroke patients with impaired myocardial swallow function by doing vokal exercises.